In My Tribe: What the Snouters (and Other Jokes) Reveal About Tribes in Science. Issue 1 (March 2019) - Cain, Joe
Highlights: Revises history of Gerolf Steiner's ficticious Rhinogradentia, or snouters, published using his pseudonym Harald Stümpke. Presents many examples in which Steiner's joke was repeated, shared, extended, and mimicked. Argues Steiner's joke is used to accomplish different types of social and intellectual work in tribes of scientists. Contributes a case study in jokelore for science. Abstract: This paper tells the history of this famous joke in science: Gerolf Steiner's invention of the Rhinogradentia using the pseudonym Harald Stümpke. It follows this story from this joke's creation in the 1940s, to the relabelling of Rhinogradentia as "snouters" in the 1960s, to later use as an inside joke within zoology and taxonomy. Steiner's original monograph for these imaginary creatures followed standard conventions in taxonomy and did not disclose its fictitious nature. It was a tall tale for specialists to cherish. Later, Steiner's joke took on a life of its own as his monograph functioned to identify communities of shared understanding and to spot lapses in expertise. This study places Steiner's story within "jokelore, " arguing the rhinograde narrative has been repeated, shared, extended, and mimicked by diverse groups so they may accomplish either social work or intellectual work within the context of particular tribes and intellectual traditions.